The effects of different plate fixation methods in the zygomaticomaxillary complex: A finite element analysis. Issue 2 (March 2020) - Fallahi, Hamid Reza; Keyhan, Seied Omid; Forooghi, Iman; Sadat Mahoutchi, Donya; Abdollahi, Mohammad Reza
Abstract: Objective: This study evaluated three different internal rigid fixation patterns' strength by finite element analysis (FEA) in a Zygomaticomaxillary complex (ZMC) fracture to find the best fixation results. Methods: This is a FEA research study of a 30-yearold man's skull cone-beam computed tomography (CBCT) imaging. The zygomatic complex fracture was simulated by the software on the model. Various fixation types were simulated on the model by Synthes miniplates in seven different methods. The resistance of each group against the average pressure of masseter and pterygoid muscles was analyzed by force importation on the muscle line axis. Results: Both the Highest Bone Movement and the Highest Average Bone Movement were related to group 1 (one plate on zygomaticofrontal suture). On the other hand, both the Lowest Bone Movement and the Lowest Average Bone Movement were related to group 6 (two plates on zygomaticomaxillary suture and inferior orbital rim). There were, however, no significant differences between the measurements. Conclusion: According to the lack of significant difference between the movements, there is no significant difference between all groups' strength.